KEMAMPUAN GURU DALAM MERANCANG TES BERBENTUK PILIHAN GANDA PADA MATA PELAJARAN IPS UNTUK UJIAN AKHIR SEKOLAH (UAS) - Purnomo, Afis (Lembaran Ilmu Kependidikan, 2007)
The research was aimed to analyze the quality of multiple choice tests ofsocial studies in the final exam for primary schools. It waws conducted in someprimary schools located in Gajah Mungkur district. The data has been analyzedquantitatively and qualitatively. The result showed that out of 45 items of the test therewere only a few good items. The majority of them didn’t meet the criterion of validity,the realibility, the level of difficulty, and the distinguishability.Kata kunci: tes, IPS, analisis